GOTO SHARE PRICE: UNUSUAL MARKET ACTIVITY AND STOCK LOCK-UP - Diky Paramitha (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
This study aims to identify unusual circumstances that occur in the movement of PT GoTo stock price during the opening of the stock lock-up and the issuance of the Unusual Market Activity (UMA) announcement. The findings in this study show that the Unusual Market Activity (UMA) Announcement issued after the stock lock-up opens does not affect long-time investors in holding their shares in trading which causes the trading frequency to increase drastically so that the stock price rises at that time and then again touches the lower auto reject (ARB). This study used a deskriptif analysis and stock price data processing with data collection techniques obtained through GoTo company financial data sources and stock prices on the IDX. The analytical method used is to analyze stock prices that occur when the stock lock-up opens until December 31, 2022. The analysis is carried out by looking at the movement of closing stock prices every day until an unusual circumstance is found so that the announcement of unusual market activity issued by the Indonesia Stock Exchange. Keywords: Lock-up, Unusual Market Activity, Stock, Auto Reject